2021
DOI: 10.21037/atm-21-657
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between peripheral reactive hyperemia index with coronary plaque burden and prognosis in patients with unstable angina pectoris complicated with type 2 diabetes mellitus

Abstract: Background: Coronary plaque burden (CPB) is an important prognostic factor in patients with unstable angina pectoris (UAP). Our current study aims to investigate the relationships between peripheral reactive hyperemia index (RHI) with CPB and prognosis in patients with UAP complicated with type 2 diabetes mellitus (T2DM). Methods:The clinical data of 187 UAP-T2DM patients who were treated in our center from June 2017 to January 2019 were retrospectively collected. RHI, CPB, and other clinical features were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…11 An 18-month follow-up study of patients with unstable angina pectoris and type 2 diabetes mellitus (T2DM) found that a decrease in peripheral RHI was associated with adverse cardiovascular events. 12 PAT also suffers from defects, such as blood flow to the peripheral vascular bed affected by autonomic tone and environment, and sensitivity to probe movement may lead to errors.The finger detection device uses disposable finger sleeves, which is slightly more expensive for clinical and research purposes.…”
Section: Vascular Assessment Indicators In Clinical Practice Vascular...mentioning
confidence: 99%
“…11 An 18-month follow-up study of patients with unstable angina pectoris and type 2 diabetes mellitus (T2DM) found that a decrease in peripheral RHI was associated with adverse cardiovascular events. 12 PAT also suffers from defects, such as blood flow to the peripheral vascular bed affected by autonomic tone and environment, and sensitivity to probe movement may lead to errors.The finger detection device uses disposable finger sleeves, which is slightly more expensive for clinical and research purposes.…”
Section: Vascular Assessment Indicators In Clinical Practice Vascular...mentioning
confidence: 99%